Additive NDDO-based atomic polarizability model - Martin, Bodo; Gedeck, Peter; Clark, Timothy (International Journal of Quantum Chemistry, 2000)
A method for the calculation of atomic polarizabilities based on the variational method for the calculation of the electronic polarizability in terms of the neglect of differential diatomic overlap (NDDO) approximation is presented. The resulting atomic polarizability tensors are additive. Calculation of an extended test set of 294 molecules gave an root-mean-square (rms) deviation between calculated and experimental mean polarizabilities of 0.68 Angstrom(3) (AM1). Comparison with the empirical atomic hybrid polarizability (AHP) parameters as defined by Miller gave good agreement. (C) 2000 John Wiley & Sons, Inc.
Keywords: atomic polarizability; group polarizability; AM1; MNDO; PM3